Chelating and antibacterial properties of chitosan nanoparticles on dentin - Aldo del Carpio-Perochena; Clovis Monteiro Bramante; Marco Antonio Hungaro Duarte; Marcia Regina de Moura; Fauze Ahmad Aouada; Anil Kishen (Korean Academy of Conservative Dentistry, 2015)
Objectives The use of chitosan nanoparticles (CNPs) in endodontics is of interest due to their antibiofilm properties. This study was to investigate the ability of bioactive CNPs to remove the smear layer and inhibit bacterial recolonization on dentin. Materials and Methods One hundred bovine dentin sections were divided into five groups (n = 20 per group) according to the treatment. The irrigating solutions used were 2.5% sodium hypochlorite (NaOCl) for 20 min, 17% ethylenediaminetetraacetic acid (EDTA) for 3 min and 1.29 mg/mL CNPs for 3 min. The samples were irrigated with either distilled water (control), NaOCl, NaOCl-EDTA, NaOCl-EDTA-CNPs or NaOCl-CNPs. After the treatment, half of the samples (n = 50) were used to assess the chelating effect of the solutions using portable scanning electronic microscopy, while the other half (n = 50) were infected intra-orally to examine the post-treatment bacterial biofilm forming capacity. The biovolume and cellular viability of the biofilms were analysed under confocal laser scanning microscopy. The Kappa test was performed for examiner calibration, and the non-parametric Kruskal-Wallis and Dunn tests (p < 0.05) were used for comparisons among the groups. Results The smear layer was significantly reduced in all of the groups except the control and NaOCl groups (p < 0.05). The CNPs-treated samples were able to resist biofilm formation significantly better than other treatment groups (p < 0.05). Conclusions CNPs could be used as a final irrigant during root canal treatment with the dual benefit of removing the smear layer and inhibiting bacterial recolonization on root dentin.